Inclusive pion and η production in p+Nb collisions at 3.5 GeV beam energy - HADES collaboration (97 authors) (2013)
Data on inclusive pion and η production measured with the dielectron spectrometer HADES in the reaction p+93Nb at a kinetic beam energy of 3.5 GeV are presented. Our results, obtained with the photon-conversion method, supplement the rather sparse information on neutral-meson production in proton-nucleus reactions existing for this bombarding energy regime. The reconstructed e+e−e+e− transverse-momentum and rapidity distributions are confronted with transport-model calculations, which account fairly well for both π0 and η production.